2007
DOI: 10.2172/925589
|View full text |Cite
|
Sign up to set email alerts
|

Demand Response Spinning Reserve Demonstration

Abstract: The Demand Response Spinning Reserve project is a pioneering demonstration of how using existing utility load-management assets can provide an important electricity system reliability resource known as spinning reserve. Providing spinning reserve with aggregated demand-side resources such as those illustrated in this report will give grid operators at California Independent System Operator (CA ISO) and Southern California Edison (SCE) a powerful, new tool to improve system reliability, prevent rolling blackout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
57
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 1 publication
0
57
0
Order By: Relevance
“…Though much of the work has been implemented in day-ahead programs such as Critical Peak Pricing (CPP), recent tests in the wholesale markets Participating Load Pilot (PLP) have consistently reduced loads in less than one minute (Kiliccote et al 2009). In the Demand Response Spinning Reserve Demonstration (Eto et al 2007) researchers concluded: "The project team measured full load response in less than 20 seconds and identified technical opportunities to further increase response speed". Lab and statewide field research has shown that the public Internet can be used to consistently send demand response control signals (with receipt acknowledgement) throughout the state.…”
Section: Communicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Though much of the work has been implemented in day-ahead programs such as Critical Peak Pricing (CPP), recent tests in the wholesale markets Participating Load Pilot (PLP) have consistently reduced loads in less than one minute (Kiliccote et al 2009). In the Demand Response Spinning Reserve Demonstration (Eto et al 2007) researchers concluded: "The project team measured full load response in less than 20 seconds and identified technical opportunities to further increase response speed". Lab and statewide field research has shown that the public Internet can be used to consistently send demand response control signals (with receipt acknowledgement) throughout the state.…”
Section: Communicationsmentioning
confidence: 99%
“…Because of this perceived surplus for reliability-based DR, the CAISO is encouraging projects that would allow non-generators (i.e. controllable loads) to bid into the other ancillary services market, such as regulation capacity and spinning and non-spinning reserve markets (CAISO In Eto et al (2007), it is argued that providing spinning reserves using demand-side resources is equivalent to providing these services using (supply-side) generators. Indeed, supplementing generation with demand-side resources would greatly increase the amount of contingency reserves available to the system operator.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The latter is a recent and promising research area aiming at improving resilience in power networks [3,15,16]. In a nutshell, the functioning of a power network is characterized by the system frequency, also called the mains frequency, which represents an indicator of the balance level between energy demand and supply.…”
Section: Introductionmentioning
confidence: 99%
“…With respect to the symmetric distribution ofz observe that for every inital time t and for every initial state X ∈ [−ε, ε] we need to consider symmetric initial output statẽ z = z(X, t) ∈ {0, 1}; for the other states,z is uniquely determined (and symmetric), see (15).…”
Section: Introducing a Thermostatmentioning
confidence: 99%